Corporatization of BERNAMA: it’s effectiveness towards financial performance for the year 1996-1998 / Marhamah Zabidi - Zabidi, Marhamah (Faculty of Business and Management, 2011)
Malaysian National News Agency (BERNAMA) is a news based agency that provides news report and other services that related with their main product. Initially, BERNAMA is an agency that operates under government. However, BERNAMA see their potential in corporatization in order to gain more income. In the middle of 1996, BERNAMA officially runs their business in corporatization era.